Mental Health Symptoms, Binge Drinking, and the Experience of Abuse During the COVID-19 Lockdown in Mexico - Morales Chainé, Silvia; López Montoya, Alejandra; Bosch Maldonado, Alejandro; Beristain Aguirre, Ana; Robles García, Rebeca; Garibay Rubio, Carlos Rodrigo; Astudillo García, Claudia Iveth; Lira Chávez, Isaura Angélica; Rangel Gómez, María Gudelia (Frontiers in Public Health, 2021)
The sanitary contingency caused by the COVID-19 pandemic is causally linked with negative mental health conditions in the same way that other traumatic events can detonate episodes of post-traumatic stress. The purpose of this paper is to evaluate how mental health is at risk during the lockdown and its relationship with specific consumption patterns, such as alcohol abuse and domestic violence. To reach this end, 9,361 individuals were surveyed, all of them Mexican nationals with an average age of 33 (DE=10.86). Out of this group of people, we found that 59% of them were single (5,523), 71% where women (6,693), only 46% were complying with the lockdown procedures (4,286), 50% complied partially (4,682) and 4% were not complying at all (393). An ex post facto correlational study was used, administered via a Survey for the assessment of mental health risk factors due to the COVID-19 pandemic. The survey was available through a WebApp programed by Linux®, PHP ®, HTML®, CSS ®, and JavaScript®. The results showed that attitudes such as avoidance, sadness, withdrawal, anger and anxiety were a byproduct of acute stress, which, in turn, was linked with a condition of anxiety caused by the uncertainty of an attaining or conserving a general status of good health. People who complied with the lockdown procedures saw a sudden increase of their alcohol consumption and lived through episodes of both physical and emotional violence, in contrast with those who did not go into lockdown or didn’t consume alcohol nor suffered from the effects of domestic violence. Further studies should be able to be in a position to evaluate the actual impact of the different methods of long-distance attention provided and whether these methods helped to curb the increase in the numbers of people affected by post-traumatic stress disorder.